Palliative and end-of-life care conversations in COPD: a systematic literature review - Tavares, Nuno (ERJ Open Res, 2017)
Chronic obstructive pulmonary disease (COPD) is a chronic life-limiting disorder characterised by persistent airflow obstruction and progressive breathlessness. Discussions/conversations between patients and clinicians ensure palliative care plans are grounded in patients' preferences. This systematic review aimed to explore what is known about palliative care conversations between clinicians and COPD patients. A comprehensive search of all major healthcare-related databases and websites was performed following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies were quality assessed, employing widely used quality-assessment tools, with only papers scoring moderate-to-high quality included. All relevant data were extracted. A narrative synthesis was used to analyse, process and present the final data. The findings indicated that the frequency and quality of palliative care conversations is generally poor. Patients and physicians identified many barriers and important topics were not discussed. Patients and clinicians reported tension between remaining hopeful and the reality of the patients' condition. When discussions did happen, they often occurred at an advanced stage of illness and in respiratory wards and intensive care units. In conclusion, current care practices do not facilitate satisfactory conversations about palliative care between COPD patients and clinicians. This impacts upon the fulfilment of patients' preferences at the end of life.